PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAAN SERTA IMPLIKASINYA PADA LOYALITAS PELANGGAN DI WARUNG AYAM PENYET ANAM RAWA BELONG JAKARTA BARAT - Nur Asih; Nurmin Arianto (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of product quality and price on satisfaction and its implications for customer loyalty at Warung Ayam Penyet Anam Rawa Belong, West Jakarta, both partially and simultaneously. The method used is quantitative. The population in this study of customers who purchased Ayam Penyet Anam was 31,909 customers from 2018-2022. The sampling technique using the Slovin formula obtained a sample of 100 respondents in this study. This research uses an analysis called path analysis (PA). The results of this research are that the Product Quality Variable has a standardized coefficient value of 0.219 and a significance level of 0.003 at an alpha coefficient of 5%. These results show that the significant level is less than 5% or 0.003<0.05. So this means that there is a significant influence between Product Quality (X1) on Loyalty (Y). The price variable has a standardized coefficient value of 0.309 and a significance level of 0.001 at an alpha coefficient of 5%. These results show that the significant level is less than 5% or 0.002 < 0.05. So this means that there is a significant influence between Price (X2) on Loyalty (Y). The Product Quality variable has a standardized coefficient value of 0.410 and a significance level of 0.000 at an alpha coefficient of 5%. These results show that the significant level is less than 5% or 0.000 < 0.05. So this means that there is a significant influence between Service Quality (X1) on satisfaction (Z). The Price variable has a standardized coefficient value of 0.507 and a significance level of 0.000 at an alpha coefficient of 5%. These results show that the significant level is less than 5% or 0.000 < 0.05. So this means that there is a significant influence between price (X2) on satisfaction (Z). The satisfaction variable has a standardized coefficient value of 0.384 and a significance level of 0.000 at an alpha coefficient of 5%. These results show that the significance level is less than 5% or 0.000 < 0.05. Which means there is a significant influence between satisfaction (Z) on Loyalty (Y).